Human Research Management: Effect of Covid-19 On Workers in the UK Who Have Previously Lost One or Both Arms - Kalogiannidis, Stavros; Papaevangelou, Olympia (Journal of Social Economics Research, 2021)
The study aims to establish the impact of COVID-19 on the workers who have previously lost one or both arms. The study was motivated by the increased need to establish the current status of disabled workers during the coronavirus pandemic. The study also seeks to establish the effect of change in wages and working from home during the pandemic on the productivity of workers who have lost one or both arms. The pandemic has impacted several sectors across the world, both socially and economically. However, there is limited research targeting workers with disabilities. The study adopted a cross-sectional survey design where data was collected from 100 workers from the UK using an online questionnaire. The findings indicated that working from home and changing wages reduced the productivity of these employees. Workers who remained at their workplaces reported incidences of stigma and discrimination from stressed fellow employees.